Experimental Investigation of Flexural Behavior of Damaged RC Beams Strengthened with Glass Fiber Reinforced Polymer (GFRP) Sheets - Hanifardhi; Saputra, Elvis; Yachya, Muchamad Amirul (Bulletin of Civil Engineering, 2026)
Indonesia is located in the Pacific Ring of Fire, an area with high tectonic and volcanic activity. This condition frequently triggers earthquakes that can damage infrastructure. Structural damage caused by earthquakes can reduce the strength, stability, and service life of buildings, necessitating effective rehabilitation measures. One promising strengthening method involves the use of composite materials such as Fiber Reinforced Polymer (FRP). Studies on GFRP retrofitting in post-damage conditions remain limited, especially for Indonesian construction practices. This study aims to evaluate the effectiveness of Glass Fiber Reinforced Polymer (GFRP) in strengthening reinforced concrete beams with reduced load-bearing capacity. The specimens consisted of a normal reinforced concrete beam without strengthening (BN), a beam subjected to a 50% reduction in initial flexural capacity and then strengthened with GFRP (BR1), and a beam with a 75% reduction in flexural capacity followed by GFRP strengthening (BR2). Flexural testing was conducted using a two-point loading method in accordance with SNI 4431-2011. The results showed that the GFRP-strengthened beams were able to sustain higher loads than the control beam, with capacity increases of 13.61% and 9.45% for the 50% and 75% reduction conditions, respectively. The maximum flexural moment of the strengthened beam reached 22.029 kNm, exceeding that of the control beam at 19.711 kNm. However, brittle deformation occurred after reaching peak strength, indicating the limited ductility of GFRP. In conclusion, the use of GFRP is effective in enhancing the flexural capacity of reinforced concrete beams, although it still presents limitations in terms of ductility